Evaluation of Platelet-Rich Plasma Therapy for Peripheral Nerve Regeneration: A Critical Review of Literature - Wang, Sulong; Liu, Xilin; Wang, Yueshu (Frontiers in Bioengineering and Biotechnology, 2022)
Peripheral nerve injury（PNI） is a common disease in clinic, and the regeneration process of peripheral nerve tissue is slow, and patients with PNI often suffer from the loss of nerve function. At present, related research on the mechanism of peripheral nerve regeneration has become a hot spot, and scholars are also seeking a method that can accelerate the regeneration of peripheral nerve. Platelet-rich plasma(PRP) is a platelet concentrate extracted from autologous blood by centrifugation, which is a kind of bioactive substance. High concentration of platelets can release a variety of growth factors after activation, and can promote the proliferation and differentiation of tissue cells, which can accelerate the process of tissue regeneration.The application of PRP comes from the body, there is no immune rejection reaction, it can promote tissue regeneration with less cost , it is ,therefore, widely used in various clinical fields. At present, there are relatively few studies on the application of PRP to peripheral nerve regeneration. This article summarizes the literature in recent years to illustrate the effect of PRP on peripheral nerve regeneration from mechanism to clinical application, and prospects for the application of PRP to peripheral nerve.